THE ROLE OF AI IN CONTEMPORARY ART: CAN AI WORK BE CONSIDERED "ORIGINAL" ART? - Putra, Edy Semara (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
The development of artificial intelligence (AI) in contemporary visual arts has presented both challenges and opportunities. This study examines the role of AI in art creation and its legal and ethical implications, particularly regarding copyright and originality. Using a qualitative descriptive method through literature review, this research analyzes how AI influences the definition of art and the role of artists in the digital era. The findings indicate that AI can serve as a creative tool that expands artistic exploration but raises debates over the authenticity and copyright of AI-generated works. Furthermore, this study recommends clearer regulations regarding the ownership of AI-based artworks to provide legal certainty for artists and technology users.